2018
DOI: 10.12890/2018_000834
|View full text |Cite
|
Sign up to set email alerts
|

Low Back Pain: A Pain That May Not Be Harmless

Abstract: Abdominal aortic aneurysms are defined as vascular dilatations greater than 50% of the normal proximal segment or those that have a maximum diameter above 3 cm. Risk factors include male gender, age over 75 years, history of vascular pathology, hypertension and arteriosclerosis. The Authors describe a case of a 74-year-old man, evaluated in an emergency setting for right lumbar pain lasting 4 days. The pain did not respond to analgesia and became progressively worse. Due to the severity of symptoms, CT angiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“… 5 Patients with chronically contained rupture of aneurysms are hemodynamically stable and have a long history of back or loin pain with symptoms attributable to compressive or erosive effect. 6 In fact, as in this case, the rupture may occur within a contained space such as the retroperitoneum or the psoas muscle space, leading to the patient being stable at presentation and often for longer. 5 Booth and Galland 7 reported that the clinical features of contained AAA rupture are vague with back pain in 64% of cases, abdominal pain in 20%, groin pain in 14%, femoral neuropathy in 8%, sepsis in 10%, and asymptomatic in 8%.…”
Section: Discussionmentioning
confidence: 84%
“… 5 Patients with chronically contained rupture of aneurysms are hemodynamically stable and have a long history of back or loin pain with symptoms attributable to compressive or erosive effect. 6 In fact, as in this case, the rupture may occur within a contained space such as the retroperitoneum or the psoas muscle space, leading to the patient being stable at presentation and often for longer. 5 Booth and Galland 7 reported that the clinical features of contained AAA rupture are vague with back pain in 64% of cases, abdominal pain in 20%, groin pain in 14%, femoral neuropathy in 8%, sepsis in 10%, and asymptomatic in 8%.…”
Section: Discussionmentioning
confidence: 84%
“…Multiple case reports have also reported severe LBP in patients with abdominal aortic aneurysms and state this as an often-overlooked differential diagnosis. 5,11,22,31 Similarly, 1 study showed improved LBP after surgical treatment of abdominal aortic aneurysms in patients with high aortic occlusion, and they concluded an ischemic component of LBP in those patients. 30 Although some studies report an association between AAC and severity of disk degeneration, we did not find any differences.…”
Section: Discussionmentioning
confidence: 99%